Jobs and Growth : Analytical and Operational Considerations for the Fund. (Policy Papers; Policy Paper ;, 2013)
Job creation and growth with inclusion are imperatives that resonate today in every country. While some advanced countries face the challenge of supporting aggregate demand with limited fiscal space in the aftermath of the Great Recession, many countries have to address ways to generate growth and create jobs in the face of the strong ongoing global megatrends of technological change, globalization, and significant shifts in demographic trends. The latter includes rapid population aging in some parts of the world, and the entry of a large number of new workers into the labor force in others. Low female labor force participation represents a significant missed opportunity to strengthen economic development and growth in many countries.